Cell non-autonomous regulation of cerebrovascular aging processes by the somatotropic axis - Bickel, Marisa A.; Csik, Boglarka; Gulej, Rafal; Ungvari, Anna; Nyul-Toth, Adam; Conley, Shannon M. (Frontiers in Endocrinology, 2023)
Age-related cerebrovascular pathologies, ranging from cerebromicrovascular functional and structural alterations to large vessel atherosclerosis, promote the genesis of vascular cognitive impairment and dementia (VCID) and exacerbate Alzheimer’s disease. Recent advances in geroscience, including results from studies on heterochronic parabiosis models, reinforce the hypothesis that cell non-autonomous mechanisms play a key role in regulating cerebrovascular aging processes. Growth hormone (GH) and insulin-like growth factor 1 (IGF-1) exert multifaceted vasoprotective effects and production of both hormones is significantly reduced in aging. This brief overview focuses on the role of age-related GH/IGF-1 deficiency in development of cerebrovascular pathologies and VCID. It explores the mechanistic links among alterations in the somatotropic axis, specific macrovascular and microvascular pathologies (including capillary rarefaction, microhemorrhages, impaired endothelial regulation of cerebral blood flow, disruption of the blood brain barrier, decreased neurovascular coupling, and atherogenesis) and cognitive impairment. Improved understanding of cell non-autonomous mechanisms of vascular aging is crucial to identify targets for intervention to promote cerebrovascular and brain health in older adults.